El Salvador - Rural Schools Triple Enrollment and Deliver Higher Quality - World Bank (Washington, DC, 2012)
Education requires sustained and well-sequenced efforts to bring about tangible results. The recently completed Secondary Education Project in El Salvador builds upon earlier programs designed to improve both the coverage and quality of primary education and has been successful in achieving similar improvements at the secondary level. Looking back, the following factors have contributed to the success of the Secondary Education Project in El Salvador: strong country ownership and long term vision; involving stakeholders; and focus on results.